Comparative Study of Griya Hasanah Product Usage and Interest Rate Impact at Bank Syariah Indonesia KCP Batam Raden Patah - Ahmad Andrevi Alrasyidin; Nahrul Hayati (LPPM-ITEBA, 2024)
The Griya Hasanah product is a home installment financing option offered by Bank Syariah Indonesia, designed to facilitate customers in purchasing a house through credit payments. This study aims to determine whether there is a difference in the number of customers using the Griya Hasanah product each month and to assess whether interest rates have an impact on the number of customers. The research method used is quantitative, with data collection techniques involving secondary data provided by Bank Syariah Indonesia KCP Batam Raden Patah. Data analysis was conducted using linear regression tests and one-way ANOVA tests. Based on the data analysis, the first conclusion drawn is that there is no significant difference in the number of customers using the Griya Hasanah product. The second conclusion is that changes in interest rates do not have a significant impact on the number of customers using the Griya Hasanah product.